UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS XI IPA SMAN 1 PAINAN MELALUI PEMBELAJARAN TTW - Syafti, Okviani; Ekaputri, Yanti Nazmai; Sefrinal, Sefrinal; Yuliana, Yuliana (STKIP Pesisir Selatan, 2023)
Mathematical communication is very important for students to have. But in fact, based on the observations made, there are still many students who have low mathematical communication skills. This is known based on interviews with several teachers who teach in high schools. For this reason, researchers carried out a treatment by applying a learning strategy that aims to be able to improve students' mathematical communication abilities. This type of research is classroom action research. The class where the research was conducted was class XI IPA 5 at SMAN 1 Painan which consisted of 30 students. Based on the test results, observation and data analysis as well as discussion in the study, it was obtained 1) The average test score in cycle I was 70.71 and cycle II was 81.93. The percentage of class completeness in cycle I was 19.28%. and cycle II of 19.28%. This shows that students' mathematical communication skills in writing have increased but have not yet reached the specified indicators. 2) The total average score of mathematical communication skills in the first cycle was 2.17 in the fairly good category and in the second cycle was 4.78 in the very good category. This shows that students' mathematical communication skills have increased and have reached the specified indicators. 3) The total average score of the results of the KBM observations in the first cycle was 3.04 in the good category and in the second cycle was 4.28 in the very good category. This shows that the teacher's ability to apply cooperative learning type think talk write (TTW).